Bridging youth ‘media egocentrism’ and journalistic values: strategies for public service media - Prieto-Arosa, Juan Manuel; d’Haenens, Leen (Frontiers in Communication, 2025)
Public service media (PSM) in Europe continues to grapple with redefining its role in a rapidly evolving media landscape, balancing quality and accessibility while striving to engage diverse audiences—including younger and marginalized groups—in an increasingly market-driven environment. This study examines how the Belgian public service media organization, Radio-Télévision Belge de la Communauté Française (RTBF), confronts the challenge of aligning journalistic values with content tailored for a youth audience marked by pronounced ‘media egocentrism.’ Employing non-participant observation and in-depth interviews with RTBF staff, the research studies the internal processes and professional practices that shape youth-focused programming. Findings reveal that RTBF integrates journalistic principles from the earliest stages of program development, effectively balancing media appeal with news integrity. This approach not only enhances RTBF’s credibility among young audiences but also cultivates critical and informed awareness within this demographic.